1987
DOI: 10.2307/1368756
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Dialects and Their Possible Relation to Honest Status Signalling in the Brown-Headed Cowbird

Abstract: We describe dialects in the flight whistle of the Brown-headed Cowbird and contrast previous hypotheses for the maintenance of dialects with a new one that assumes that a male' s ability to give the correct local dialect is an honest signal of relatively high male quality. The three dialects upon which we focus are part of an extensive dialect system along the eastern Sierra Nevada. The dialects are partially isolated by unsuitable habitat and are unusual because they differ via lexical rather than the less ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(115 citation statements)
references
References 31 publications
(57 reference statements)
3
112
0
Order By: Relevance
“…The issue of how local dialects are maintained and whether they have signi cant evolutionary consequences has been the subject of intense interest and controversy in recent years (summarized in Kroodsma et al, 1984;Baker & Cunningham, 1985;Rothstein & Fleischer, 1987). Catchpole & Rowell (1993) have shown that in the case of local dialects in a population of the European wren (Troglodytes troglodytes), a small yet signi cant natural boundary, such as a 200 meter wide lake, is all that is needed for separate song traditions to develop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of how local dialects are maintained and whether they have signi cant evolutionary consequences has been the subject of intense interest and controversy in recent years (summarized in Kroodsma et al, 1984;Baker & Cunningham, 1985;Rothstein & Fleischer, 1987). Catchpole & Rowell (1993) have shown that in the case of local dialects in a population of the European wren (Troglodytes troglodytes), a small yet signi cant natural boundary, such as a 200 meter wide lake, is all that is needed for separate song traditions to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Some species show a geographical mosaic of local populations, each characterized by distinctive variants of a given vocalization. These different groups of individuals constitute 'dialects' which may be de ned as separate, adjacent aggregations of birds, with wellde ned boundaries, and with different vocalizations (Rothstein & Fleischer, 1987). The variations in bird song may even occur on a microgeographic scale, between neighboring groups of birds, which might, at least potentially, interact or interbreed with each other (reviewed in Mundinger, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is sometimes equated with the "acoustic adaptation hypothesis" (Rothstein & Fleischer 1987) wherein songs, especially dialects or song neighborhoods (Payne et al 1988) arise because some song characteristics propagate better than others in specific habitats.…”
Section: Ranging: the Avian Perception Of Distancementioning
confidence: 99%
“…If males are unlikely to switch song syntax after early exposure to song variants exhibiting a particular syntactical rule, and females tend not to switch their syntax preferences from those acquired when they are young, both of which are suggested by the available data (14)(15)(16)(17), then songs may serve as "population markers"-either as a population recruitment device, with young males and females preferentially breeding in locations with songs similar to their natal area (25), or as a device that limits immigration of adult birds (26).…”
Section: Discussionmentioning
confidence: 98%